Proceedings of the 23rd Conference on Computational Natural Language Learning (CoNLL) 2019
DOI: 10.18653/v1/k19-1049
|View full text |Cite
|
Sign up to set email alerts
|

Learning Dense Representations for Entity Retrieval

Abstract: We show that it is feasible to perform entity linking by training a dual encoder (two-tower) model that encodes mentions and entities in the same dense vector space, where candidate entities are retrieved by approximate nearest neighbor search. Unlike prior work, this setup does not rely on an alias table followed by a re-ranker, and is thus the first fully learned entity retrieval model. We show that our dual encoder, trained using only anchor-text links in Wikipedia, outperforms discrete alias table and BM25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
178
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 167 publications
(180 citation statements)
references
References 25 publications
2
178
0
Order By: Relevance
“…Basing entity representations on features of their Wikipedia pages has been a common approach in EL (e.g. Sil and Florian, 2016;Francis-Landau et al, 2016;Gillick et al, 2019;Wu et al, 2019), but we will need to generalize this to include multiple Wikipedia pages with possibly redundant features in many languages.…”
Section: Mel With Wikidata and Wikipediamentioning
confidence: 99%
See 2 more Smart Citations
“…Basing entity representations on features of their Wikipedia pages has been a common approach in EL (e.g. Sil and Florian, 2016;Francis-Landau et al, 2016;Gillick et al, 2019;Wu et al, 2019), but we will need to generalize this to include multiple Wikipedia pages with possibly redundant features in many languages.…”
Section: Mel With Wikidata and Wikipediamentioning
confidence: 99%
“…Prior work showed that a dual encoder architecture can encode entities and contextual mentions in a dense vector space to facilitate efficient entity retrieval via nearest-neighbors search (Gillick et al, 2019;Wu et al, 2019). We take the same approach.…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to interaction-based models, which are applied to query-document pairs, our approach is to decouple entity encoding and document encoding. Therefore we follow recent work in representation-based Entity Linking [14] and embed textual knowledge from the clinical domain into this representation. Our goal is to generalize entity representations, so the model will be able to align to existing taxonomies without retraining.…”
Section: Entity Spacementioning
confidence: 99%
“…The model uses multi-task learning [9] to align the sequence of sentences in a long document to the clinical knowledge encoded in pre-trained entity and aspect vector spaces. We use 1 Code and evaluation data is available at https://github.com/sebastianarnold/cdv a dual encoder architecture [15], which allows us to precompute discourse vectors for all documents and later answer ad-hoc queries over that corpus with short latency [14]. Consequently, the model predicts similarity scores with sentence granularity and does not require an extra inference step after the initial document indexing.…”
Section: Introductionmentioning
confidence: 99%